PKH Conditional Cash Transfer - World Bank (World Bank, Jakarta, 2017)
This is a first for Indonesia: Program Keluarga Harapan (PKH) is the only household-targeted social assistance initiative to have designed randomized impact evaluation into the initial allocation of the program. This brings three major benefits for policymakers: 1) the evidence available for evaluating the impacts of the PKH program on household welfare is extensive and sound; 2) the program design and the impact analysis design have generated additional excitement, both nationally and internationally, about the program, its goals and social assistance initiatives in general; and 3) the results and underlying data will be made publicly available, which has already spurred interest in additional evaluations that will stock the shelves of social assistance policy research libraries. PKH's success in delivering real benefits to the very poor and in changing behaviors deserves further support and encouragement. PKH's initial weaknesses in implementation and delivery deserve continuing attention and thoughtful solutions for greater effectiveness. The Government of Indonesia (GOI) plans on expanding the PKH program to as many as three million households; while it is doing so, it should continue to refine implementation, coordinate and collaborate with affiliated service providers in health, education, and local government services, and continue developing a corps of organized, enthusiastic, and skilled facilitators who can assist very poor households in achieving healthier behaviors.